Brown Adipose Tissue Activation in Humans Increases Plasma Levels of Lipid Mediators - Walker, Mary E; Kodani, Sean D; Mena, Hebe Agustina; Tseng, Yu-Hua; Cypess, Aaron M; Spite, Matthew (The journal of clinical endocrinology and metabolism, 2024)
Abstract Context Activation of brown adipose tissue (BAT) thermogenesis improves insulin sensitivity and is beneficial in obesity. Emerging evidence indicates that BAT activation increases lipid mediators that play autocrine and endocrine roles to regulate metabolism and inflammation. Objective The goal of the study was to determine the relationship between 2 distinct approaches of BAT activation (cold exposure and mirabegron treatment) with lipid mediators in humans. Methods Healthy female subjects (n = 14) were treated with the β3-adrenergic receptor agonist mirabegron (100 mg) daily for 28 days. A subset of female subjects (n = 8) was additionally exposed to cold temperatures (14-16 °C) for 2 hours using a cooling vest prior to initiating mirabegron treatment. A panel of lipid mediators was assessed in plasma using targeted liquid chromatography-tandem mass spectrometry, and their relationship to anthropometric and metabolic parameters was determined. Results Activation of BAT with cold exposure acutely increased levels of lipoxygenase and cyclooxygenase products, including 12-hydroxyeicosapentaenoic acid, 12-hydroxyeicosatetraenoic acid (HETE), 5-HETE, 14-hydroxydocosahexaenoic acid (HDHA), an isomer of maresin 2 (MaR2), 17-HDHA, protectin D1 (PD1), and prostaglandin E2. Mirabegron treatment similarly increased these products acutely, although levels of some mediators were blunted after chronic mirabegron treatment. Selected lipid mediators, including an MaR2 isomer, 17-HDHA, 5-HETE, and 15-HETE, positively correlated with nonesterified fatty acids and negatively correlated with the respiratory quotient, while PD1, 15-HETE, and 5-HETE positively correlated with adiponectin. Conclusion These results indicate that selected lipid mediators may serve as biomarkers of BAT activation.